PEMERINTAH DAN LITERASI KEUANGAN: PERAN PENTING DEMI MASA DEPAN FINANSIAL UMKM BERBASIS OVOP - ARINA HIDAYATI; Tabah Rizki; Triyono Triyono (Jurnal Akuntansi dan Bisnis, 2025)
The poverty rate in Batang Regency remains high. One of the government's strategies to address this issue is through the implementation of the One Village One Product (OVOP) program, which aims to develop and promote distinctive products from each MSME across regions. However, a major weakness identified in the OVOP program is the limited access to capital among MSME owners, which constitutes a significant responsibility for the government. Strengthening MSME business capital can be achieved through loan facilitation and improved financial management practices, particularly by enhancing financial literacy. This study, based on a literature review with a qualitative approach, utilizes primary and secondary data from various sources. The findings reveal that OVOP-based MSMEs in Batang Regency demonstrate financial literacy rates as follows: (1) 50–70% possess knowledge of financial recording and management, and (2) a portion has systematically recorded business income and expenses. While these two aspects of financial literacy are relatively well adopted, knowledge related to financial access remains under 60%. The government's role in promoting financial literacy has so far been limited to educational and socialization activities, which have not been conducted consistently or sustainably